Precision genetics tools for genetic improvement of banana - Tripathi, J.; Ntui, V.O.; Tripathi, L. (Wiley, 2024)
Banana is an important food security crop for millions of people in the tropics but it faces challenges from diseases and pests. Traditional breeding methods have limitations, prompting the exploration of precision genetic tools like genetic modification and genome editing. Extensive efforts using transgenic approaches have been made to develop improved banana varieties with resistance to banana Xanthomonas wilt, Fusarium wilt, and nematodes. However, these efforts should be extended for other pests, diseases, and abiotic stresses. The commercialization of transgenic crops still faces continuous challenges with regulatory and public acceptance. Genome editing, particularly CRISPR/Cas, offers precise modifications to the banana genome and has been successfully applied in the improvement of banana. Targeting specific genes can contribute to the development of improved banana varieties with enhanced resistance to various biotic and abiotic constraints. This review discusses recent advances in banana improvement achieved through genetic modification and genome editing.